The impact of dietary phosphorus levels on growth, slaughter, and digestive metabolism in growing sheep - Shoupei Zhao; Xiaojun Ni; Jia Zhou; Xiaoqi Zhao; Xiao Wen; Xiaolin Wang; Mingyu Cao; Yanfei Zhao; Chong Shao; Lianghao Lu; Yuanyuan Chen; Bao Zhang; et al. (Frontiers in Veterinary Science)
Phosphorus (P) pollution from livestock farming poses significant environmental challenges, necessitating efficient P utilization. This study systematically investigated the effects of varying dietary P levels on growth, slaughter performance, nutrient digestion, and metabolism in Yunnan Semi-fine Wool Sheep during the growth phase. Forty-five sheep (30.33 ± 0.56 kg) were randomly assigned to five dietary P levels (0.40, 0.51, 0.68, 0.82, and 0.97%) over a 44-day trial, including a 14-day pre-feeding and 30-day formal trial period. Digestibility trials were conducted on days 22–27, and selected sheep were slaughtered for detailed analysis. Results showed no significant effects of dietary P on daily weight gain, feed-to-gain ratio, or organ indices (p > 0.05). However, dry matter intake, liver, and lung weights decreased linearly with increasing P levels (p < 0.05). Carcass traits such as left half carcass rate and net rib rate varied significantly (p < 0.05), showing quadratic trends. P levels also affected P, calcium, protein, and energy metabolism, as well as apparent digestibility of acid detergent fiber (p < 0.05). Using endogenous loss and comparative slaughter methods, the P maintenance requirement was determined as: Retained p = 0.5436 × Intake P – 0.0614 (R2 = 0.83, p < 0.01). P requirements for growth were modeled as: P (g/kg EBW) = 30.95772 × EBW – 0.5031. The recommended dietary P level was 0.40%, with maintenance and growth requirements of 0.06 g/EBW and 5.34–6.19 g/kg EBW, respectively, providing a foundation for P reduction strategies.